'Without Being Walt Whitman': Vicente Huidobro, Whitman, and the Poetics of Sight. - Franklin, Kelly Scott (Comparative American Studies, 2014)
The Chilean vanguardista poet Vicente Huidobro singlehandedly inaugurated the Spanish-language avant-gardes with his 1918 poem Ecuatorial [ Equatorial], and remained a dynamic and controversial global figure until his death in 1948. This essay demonstrates how Huidobro appropriated Walt Whitman's 'Salut au Monde' into this inaugural poem, taking from the US poet an elevated, comprehensive poetics of sight. But Whitman's all-seeing aesthetic seriously threatened Huidobro's own ethics and avant-garde poetic philosophy - Creationism - leading the Chilean to reject Whitman and this poetic vision in his 1931 Altazor. If Whitman's poetic speaker could 'contain multitudes', seeing the whole world in instant juxtaposition, Huidobro's ideal Creationist poet must instead empty himself, to create anew. Finally, this textual and historical confrontation reveals not only how Whitman brought his unifying vision to bear on his nation's Civil War, but also how the aging Huidobro, facing World War II and the imperialist shadow of the US, wrote back to Whitman to qualify and clarify what this vision might mean for 'America'.